Membrane cholesterol modulates oligomeric status and peptide-membrane interaction of severe acute respiratory syndrome coronavirus fusion peptide - Meher, Geetanjali (2022)
The N-terminal fusion peptide (residues 770-788) of an S2 glycoprotein of the severe acute respiratory syndrome coronavirus (SARS-CoV), exposed upon receptor binding, is crucial for virus entry into the host cell. The fusion peptide alters the membrane organization and dynamics of the host membrane to facilitate membrane fusion. Generally, the effect of the fusion peptide on the membrane is sensitive to the lipid composition of target membranes. In the present work, we have utilized steady-state and time-resolved fluorescence spectroscopy in tandem with circular dichroism spectroscopy to elucidate the binding, oligomeric status, and secondary structure of the fusion peptide and its impact on the depth-dependent membrane organization and dynamics. We have used depth-dependent fluorescence probes, 1,6-diphenyl-1,3,5-hexatriene (DPH) and its trimethylammonium derivative (TMA-DPH), to evaluate the effect of the peptide binding along the bilayer normal. We have exploited the energy transfer efficiency of tryptophan between TMA-DPH and DPH to determine the relative location of the solitary tryptophan present in the membrane-bound fusion peptide. We have further evaluated the effect of membrane cholesterol on the binding and organization of the peptide and the impact of peptide binding on the depth-dependent physical properties of the membrane at various cholesterol concentrations. Our results clearly demonstrate that the membrane cholesterol alters the oligomeric status of the membrane-bound peptide and the effect of peptide binding on the depth-dependent membrane organization and dynamics. The role of cholesterol is important, as the eukaryotic host cells contain a good amount of cholesterol that might be important for the entry of pathogenic viruses.